Pembelajaran Pendidikan Agama Islam Berbasis Ekoteologi: Penguatan Kesadaran Lingkungan di SMA Negeri 1 Jati Agung - Latifah Nurrahma Dewi; Subandi; Ais Isti'ana (WISE Pendidikan Indonesia, 2026)
Environmental awareness is an important concern in Islamic Religious Education because students are expected not only to understand religious teachings conceptually but also to apply them through responsible attitudes toward nature and the school environment. This study aimed to analyze the integration of ecotheological values in Islamic Religious Education learning and their role in fostering students’ environmental awareness at SMA Negeri 1 Jati Agung. This study employed a qualitative descriptive approach. The participants consisted of one Islamic Religious Education teacher and 10 students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed thematically through data reduction, data display, and conclusion drawing. Data credibility was strengthened through triangulation of data collection techniques. The findings showed that ecotheological values were integrated through contextual explanations connecting Islamic teachings with environmental responsibility, environmental-based learning activities, teacher role modeling, school cleanliness programs, classroom duty schedules, Friday cleaning activities, and creative assignments related to environmental care. Supporting factors included school policies, teacher commitment, student participation, and the availability of environmental facilities. However, the implementation was constrained by inconsistent student awareness, limited instructional media, and restricted learning time. These findings indicate that integrating ecotheological values into Islamic Religious Education can strengthen students’ understanding of environmental responsibility as part of religious practice. Effective implementation requires consistent teacher modeling, supportive school policies, adequate learning resources, and continuous environmental habituation.